Optimizing psychological interventions for trichotillomania (hair-pulling disorder): an update on current empirical status - Snorrason I; Berlin GS; Lee HJ (Psychology Research and Behavior Management, 2015)
Ivar Snorrason, Gregory S Berlin, Han-Joo Lee Department of Psychology, University of Wisconsin-Milwaukee, Milwaukee, WI, USA Abstract: Trichotillomania (hair-pulling disorder) is a psychiatric condition characterized by a persistent habit of pulling out one's hair. In treatment-seeking populations, hair-pulling disorder can be severe, chronic, and difficult to treat. In the early 1970s, behavioral interventions (eg, habit reversal training) were developed and proved effective in treating chronic hair-pulling for many individuals. In order to further increase treatment efficacy and improve long-term outcome, several authors have developed augmented treatment protocols that combine traditional behavioral strategies with other cognitive-behavioral interventions, including cognitive therapy, dialectical behavioral therapy, and acceptance and commitment therapy. In the present review, we give an overview of the clinical and diagnostic features of hair-pulling disorder, describe different cognitive-behavioral interventions, and evaluate research on their efficacy. Keywords: trichotillomania, hair-pulling, cognitive-behavioral therapy, diagnosis, review